A new species of Candolleomyces (Psathyrellaceae, Agaricales) from Western Ghats, India - Nayana, P.k.; Ck, Pradeep (Phytotaxa, 2023)
Continuing survey of the Psathyrellaceae of Kerala State, India, has resulted in the discovery of a remarkable Candolleomyces species from the tropical forests. Both morphological and molecular analyses of the internal transcribed spacer (nrITS) region confirmed the novelty and placement of the species in the genus Candolleomyces. The species is described with macro and microphotographs, phylogeny and a comparison with related species of Candolleomyces.